The application of lattice gas automata for simulating polymer injection porous media - Fathaddin, Muhammad Taufiq (2006)
The simulation of polymer displacement in a reservoir is one of the important techniques in petroleum engineering that is used to predict the performance of oil production. Modeling of polymer flow through a porous medium is often derived by a macroscopic scale approach. In order to gain better insight of the polymer flow, a pore scale (mesoscale) model is applied in this thesis to determine the macroscopic properties. The objectives of this research are to develop the Frisch-Hasslacher-Pomeau (FHP) III models of lattice gas automata to simulate microscopic polymer and oil flow for the study of macroscopic properties of adsorption, gelation and polymer displacement phenomena. In the single-phase flow simulation, collision rules of interactions between polymer and solid material for adsorption and gelation processes were proposed. Correlations between various macroscopic properties such as polymer concentration, porosity, surface length, pore width were obtained. In general, the lattice gas automata simulations were in good agreement with previous studies, where the differences between them were between 2.0% to 17.4%. In the two-phase flow simulation, the displacement mechanism for various mobility ratio and adsorption rate was estimated. The change of saturation in dead-end pores during the displacement was analyzed. The results of the two-phase flow simulations were in good agreement with those of laboratory experiments, where differences of all parameters were between 3.1% to 18.4%. The computation time is a crucial factor influencing the feasibility of a mesoscale model application in simulating large porous media. Due to the nature of lattice gas automata, the simulation can run using parallel computers effectively. The use of parallel computers is able to reduce the computation time problem. In this thesis, a parallel computation technique has been proposed to run the lattice gas automata simulation. A cluster system and standalone computers were used to simulate communicating and non-communicating flow in porous media, respectively. The results of the parallel simulations were in good agreement with those of single simulations, where maximum difference of all parameters was 3.93%. The computation time was reduced by a factor that ranged from 1.9083 to 14.3411.